Changes of endophytic microbial community in Rhododendron simsii roots under heat stress and its correlation with leaf physiological indicators - Lin, Wei; Liu, Lei; Liang, Jincheng; Tang, Xuexiao; Shi, Jie; Zhang, Li; Wu, Purui; Lan, Siren; Wang, Shusheng; Zhou, Yan; Chen, XiaoChou; Zhao, Ying; et al. (Frontiers in Microbiology, 2022)
Introduction The response mechanism of Rhododendron simsii and its endophytic microorganism to heat stress is still unclear. Methods The light incubator was used to set the temperature gradients, and the control (CK) was (day/night: 14/10 h) 25/22°C, the moderate-heat-stress (MHS) was 35/30°C and the high-heat-stress (HHS) was 40/35°C. Results Compared with CK, MHS significantly increased the contents of malondialdehyde, hydrogen peroxide, proline, and soluble sugar, as well as the activities of catalase and peroxidase in leaf, while HHS increased the activities of ascorbate peroxidase, and decreased chlorophyll content. Compared with CK, MHS reduced soil available nitrogen (N) content. Both heat stress changed the endophytic microbial community structure in roots. MHS enriched Pezicula and Paracoccus, while HHS significantly enriched Acidothermus and Haliangium. The abundance of Pezicula positively correlated with the contents of chlorophyll a and proline in leaf, and negatively correlated with soil ammonium N content. The abundance of Pezicula and Haliangium positively correlated with soluble sugar and malondialdehyde contents, respectively. Conclusions Our results suggest that root endophytic microorganisms play an important role in helping Rhododendron resisting heat stress, mainly by regulating soil N content and plant physiological characteristics.